Clinical features related to rapid cycling and one-year euthymia in bipolar disorder patients: A multicenter treatment survey for bipolar disorder in psychiatric clinics (MUSUBI). (December 2020) - Kato, Masaki; Adachi, Naoto; Kubota, Yukihisa; Azekawa, Takaharu; Ueda, Hitoshi; Edagawa, Kouji; Katsumoto, Eiichi; Goto, Eiichiro; Hongo, Seiji; Tsuboi, Takashi; Yasui-Furukori, Norio; Yoshimura, Reiji; et al.
Abstract: Objective: Rapid cycling (RC) presents a risk of greater severity in bipolar disorder (BD), whereas patients with one-year euthymia (OYE) have better prognosis. The purpose of this study was to identify the clinical background and prescription characteristics of patients in the two opposing states of current RC and OYE from a large sample (N = 2609) in a multicenter treatment survey on BD in psychiatric clinics (MUSUBI). Methods: MUSIBI was a cross-sectional study wherein questionnaires, based on a retrospective medical record survey of consecutive cases of BD, were distributed to 176 outpatient clinics. The questionnaire collected information on patient background, current episode, and clinical and prescription characteristics. OYE was defined as the presence of a euthymic state for at least 12 months. Results: In this study, current RC (9.7% frequency) was significantly higher in females, had a younger age of onset, functional impairments, and a higher rate of neurodevelopmental disorder and physical comorbidity compared to non-RC patients. OYE (19.4% frequency) was associated with a lower proportion of females, older age, higher occupational status, and lower rate of suicide ideation, psychotic symptoms, personality disorder, and alcohol or substance abuse. Mood stabilizers were prescribed in ≥80% of cases, while antipsychotics were prescribed in half of the cases (more in RC and less in OYE). Antidepressant prescription rates were lower in OYE than in RC. Conclusions: RC and OYE generally show opposing characteristics, but the details of the opposite parameters are distinctive. Clinicians can help predict the progression of BD by understanding the clinical background and characteristics of these opposing clinical features. Highlights: Clinical characteristics of rapid cycling (RC) and (one-year euthymia) OYE analysis in a large sample (N = 2609). RC was associated with female sex, younger age of onset, neurodevelopmental disorders, and physical comorbidity. OYE was associated with male, older age, occupational status and lower rate of personality disorders and alcohol abuse. Antidepressant prescription rates were comparable for RC and lower for OYE.